PENGARUH MASSA SOURCE TERHADAP KETEBALAN THIN FILM MELALUI DEPOSISI VACUUM THERMAL EVAPORATION - Abidin, Kurniati; Malago, Jasruddin Daud; Noor, Fatimah Arofiati; Winata, Toto (JFT: Jurnal Fisika dan Terapannya, 2021)
Purpose of this research to determine the effect of mass of source on thickness of thin film, with using the vacuum thermal evaporation. The metal used is Ag with a purity of 99,99% as a source of evaporated metal and using glass preparations as a substrate on which metal is deposited. By using three types of characterization such as FPP, SEM and EDS, the research results were obtained accurately. Based on these characterizations, the results obtained a significant relationship between mass of source and thickness of thin film, increasing the mass of the source will increase the thickness of thin film. This result can be used as a reference in producing thin films with specific of thickness.